Formation of national identity as the basis of national security of Ukraine - Kuruch, A. (Problems of Engineer-Pedagogical Education, 2021)
The research is devoted to the topical issue "Formation of national identity". The article considers in detail the meaning of the term "national identity" substantiates the need to form it in the population, identifies the importance of the issue as a component of national security and the need to address it at the level of public policy. It is proved that the formation of national identity is a necessary condition for the functioning of civil and socially responsible society. Peculiarities of education of national identity in Ukraine are analyzed, different views of modern researchers on the formation of national identity among the population of different countries are considered. The historical aspects of the development of this issue in the world, the peculiarities of the formation of national identity in Ukraine in the light of historical events, as well as the theoretical basis for the formation of national identity and the consequences of modern global trends on the Ukrainian mentality. The stages of socialization of the individual in Ukraine, the features of each of them and their significance for the formation of national identity are described. The main problematic issues that arise during this process are identified. It is substantiated that the national identity of Ukrainians due to the long absence of their own state was a contradictory phenomenon in its content and consisted only in the content of ethnic identification, so today there is a need for new components of national identity. The article proves the necessity of introducing the program of national unity in the education of general secondary education institutions: in the conditions of modern Ukrainian realities there is an urgent need to protect one's cultural heritage, traditions and language. After analyzing current Ukrainian political trends, it was concluded that the blurred national identity, the introduced policy of regional differences of Ukrainians prevents the unification of nations in opposition to global processes in the world. The idea of this study is that in modern world trends there is a need to determine the priority national interests and external orientation of the country on the basis of national identity, otherwise the state will be doomed to ethno-national dichotomy, confrontation and identity crisis.